PENGARUH INDEPENDENSI AUDITOR PADA KAP BIG FOUR TERHADAP MANAJEMEN LABA PADA INDUSTRI BAHAN DASAR, KIMIA DAN INDUSTRI BARANG KONSUMSI - NINI NINI; ESTRALITA TRISNAWATI (Jurnal Bisnis dan Akuntansi, 2009)
This research examine the effect of professional ethics, audit fee, and non audit services to earnings management at Basic-Chemical and Consumer Good Industries that are listed in BEI. Samples are obtained by purposive sampling method and obtained 17 observation data from 2004-2008. The result indicate that professional ethics and non service audit are significantly affect the earnings management.